Abhijit Banerjee and Esther Duflo. Poor Economics: Rethinking Poverty and the Ways to End it. Gurgaon, India: Random House. 2011. 499 pages. Indian Rupees 279.00 (The Pakistan Development Review, 2013)
In “Poor Economics”, Abhijit Banerjee and Esther Duflo have put forward an interesting perspective on how to view the issue of poverty and innovative ways for its alleviation. The lessons in the book are rooted in the 15 years of authors’ research in different developing countries across the globe. They advance the debate initiated by Jeffrey Sachs and William Easterly and prudently bring out the way the poor think and behave. Based on randomised controlled trials, Banerjee and Duflo have enriched this compelling piece of work and shed light on the truth of the poverty trap. The book is divided into two main sections. The first section deals with the private lives of poor and sheds light on the ground realities. This section discusses topics like consumption, health, education and reproduction from the perspective of the poor. It addresses, in detail, questions like why poor people, when they do not have enough to eat, splurge on luxuries like television, DVD players, mobile phones etc. Although the poor do send their kids to schools but it makes no difference to their mental capacity. The authors also show that the poor do not care about medicines but they often indulge in drugs. T